Investigations on electrical and thermal transport properties of Cu2SnSe3 with unusual coexisting nanophases. (December 2018) - Zhou, Y.; Wu, H.; Wang, D.; Fu, L.; Zhang, Y.; He, J.; Pennycook, S.J.; Zhao, L.-D.
Abstract: The ternary diamond-like compound Cu2 SnSe3 is a potential thermoelectric material. Its Cu-Se conducting network leaves Sn as a likely doping site to optimize the carrier concentration without much deterioration to the carrier mobility. Thus, the precise determination on the intricate phase structures of Cu2 SnSe3 is critical. Here, we first use the atomically resolved scanning transmission electron microscopy and reveal an unusual phase coexistence (monoclinic and orthorhombic phases) in Ag-doped Cu2 SnSe3 . Owing to coexisting phases and the order–disorder transition in the orthorhombic phase, the Ag-doped Cu2 SnSe3 shows an unusual three-stage behavior in its temperature-dependent electrical transport properties and achieves record high power factors in this system. The observed three-stage behavior due to the phase coexistence is supported by the first principle calculations, Hall measurements, and optical diffuse reflectance measurements. To fully understand the band structures and the coherent interface between these coexisting phases, a band contact model is proposed that could well explain the three-stage electrical transport behavior. Moreover, the phase coexistence is observed at the nanoscale regime, thus providing a high density of phase boundaries. Such coexisting nanophases play an important role in lowering the lattice thermal conductivity. As a result, the ZT value obtained in Cu2 Sn0.93 Ag0.07 Se3 is double that of undoped Cu2 SnSe3 . Graphical abstract: A unique three-stage behavior is first observed in the temperature-dependent electrical transport properties in Cu2 SnSe3, which could effectively enhance the thermoelectric performance due to the unusual coexisting nanophases. This three-stage behavior could be well explained using one interface setup model and supported by the first principle calculations, Hall measurements, and optical diffuse reflectance measurements. Highlights: The distributions of these Cu and Sn cations are directly revealed by the atomically resolved scanning transmission microscopy. A three-stage behavior is observed in electrical properties enhancing the PF due to the unusual coexisting nanophases. A significant decrease in the high-temperature lattice thermal conductivity due to the high-dense nanophases is observed.